AKTIVASI PERAN MAHASISWA KKN UINSU 125 DALAM PENINGKATAN PENDIDIKAN DAN KESEHATAN DIDESA SIBOLANGIT - Dini Anggraini Srg; Karina Nurfebia, Dimas Pratama, Hafizul Mughiroh, Ety Jumiaty (CV. Adiba Aisha Amira, 2024)
Sibolangit Village is one of the tourist villages in North Sumatra, this village is located in the Deli Serdang Regency, North Sumatra Province. Educational limitations in terms of accessing the latest learning information create quite difficult challenges for several schools in Sibolangit Village. The health of the elderly is also a special concern there. The method of implementing Real Work Lecture (KKN) activities for North Sumatra State Islamic University students to the community consists of the work program JBT (Additional Study Hours), JBM (Evening Study Hours), JBP (Companion Study Hours), Koran Learning, elderly health and stunting education . All the programs carried out have run well which can be seen from the enthusiasm of students in participating in all the programs that have been created. in following all the programs that have been created and the same is true for elderly people who regularly take part in exercise activities and mothers and children who take part in posyandu and counseling.